Profil anthropométrique des joueuses des équipes de France féminine de rugby à XV et à VII - Pingon, M.; Loursac, R.; Girardin, J.; Lustig, S.; Servien, E. (Science & Sports, 2023)
Women's rugby is a team sport which raising interest enabled its recent professionalisation. In this sport, it has been shown that performances in male players depended on their body composition. However, only a few studies analysed female players. The aim of this study is to determine and compare body composition as well as anthropometric variables in the players of the French Women's XV's and VII's Team.